2018
DOI: 10.1039/c7tb02636f
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine–polyethylene glycol–albumin antifouling coatings on multiple substrates

Abstract: Polydopamine–PEG coatings on different substrates: effects of PDA layer properties on PEG grafting and anti-biofouling properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…The C 1s spectra (Fig. 4 a ) that exhibits three peaks can be assigned to the C–C, C–N, and C–O bonds in PDA structure [17]. Part of the peak at 284.6 is attributed to the residual carbon from the XPS instrument itself.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C 1s spectra (Fig. 4 a ) that exhibits three peaks can be assigned to the C–C, C–N, and C–O bonds in PDA structure [17]. Part of the peak at 284.6 is attributed to the residual carbon from the XPS instrument itself.…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine, a mussel-inspired biomolecule, can generate adhesive polydopamine (PDA) films and easily deposited onto virtually any substances [15][16][17]. Therefore, it is commonly used to generate PDA coating and immobilise metal NPs [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies attempted to use PDA to prepare various coatings, including antibacterial coating, 48 anticoagulation coating, 49 and antifouling coating. 50 However, there were few reports on the use of PDA as the coating of the cell sheet detachment. With respect to the concentration of dopamine for the synthesis of PDA coating has been explored by a large number of studies and demonstrated that the optimal concentration was 2 g/L, 51,52 whereupon 2 g/L dopamine was used to synthesize the PDA coating.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the significant increase in surface roughness of pDA coatings caused by the inevitable aggregation of oligo-DA micro-/nano-particles may limit their application in some fields with special requirements for surface roughness, e.g. biosensors [ 11 ]. Some researchers tried to make some changes by adjusting the pH value, changing the dopamine concentration, replacing the buffer system, etc., to achieve smoother pDA coatings but with little success [ 12 ].…”
Section: Introductionmentioning
confidence: 99%